Ambient air cereal grain drying – Simulation of the thermodynamic and microbial behavior. (October 2019) - Schemminger, Jörg; Mbuge, Duncan; Hofacker, Werner
Highlights: The ambient air drying pattern can be predicted from climatic data parameters. With knowledge of the initial contamination toxin formation can be predicted. Time and costs can be reduced using the simulation tool instead of experiments. Abstract: The thermodynamics of ambient air cereal drying processes have been investigated and resulted in an accurate model to predict the drying behavior. Microorganism growth and the production of toxins have been separately investigated as well. Combining both models of thermodynamics and biology allows for the description of ambient temperature grain drying processes aiming at preservation without the need of long-term/high-cost-experiments. The agreement of simulated and experimental data has been verified and confirms the applicability of the model regarding thermodynamic and microbial behavior under continuous drying operations. Transferring the simulation on low-tech-bin-dryers showed a production of toxins that approximately doubled during the drying process when the fill level of maize inside the bin dryer was compared between half and completely filled.